SMFA Senior Thesis Project May, 2017. - Grossman, Ellie. (Tufts Archival Research Center, 2017)
Through the exploration of the relationship between perception and mental processes, I investigate how each manifest within the other to affect judgment, perception, and meta-perception. I embark on this exploration through my own mental processes, utilizing my color synesthesia - "a crossing over of the senses", allowing me to associate people with color-to overlay my own perceptions of the individuals and interactions I experience. By acknowledging my own subjectivity in communication, it conversely allows me to employ an objective lens through which I can decipher interaction. A preliminary conversation with the subject serves to gather information and foster connection, as they detail how their individual mind affects their perception of themselves and others. I then incorporate my personal language of color, creating a portrait that establishes a visual representation of my attempt to "accurately'' join our perceptions. Following the creation of the portrait, a subsequent conversation takes place in its presence as the subject and I discuss the correctness of the perception created: Is this accurate? Where is the disparity? What affect does this have on personal perception versus external? Recordings of the epilogue conversations play along with the portraits, discernable in close proximity, yet imperceptible while viewing the paintings in totality. Perhaps melancholically, it becomes apparent that there is no truly impartial image, as neither I or the subject can ever achieve perfect objectivity in this self-reflection.; Keywords: psychology, mental health, identity, perception, oil paint, painting.